Asthma and Allergies in the School Environment - Esty, Brittany (Clin Rev Allergy Immunol, 2019)
The school is a complex microenvironment of indoor allergens, pollutants, and other exposures. The school represents an occupational model for children and exposures in this environment have significant health effect. Current research establishes an association between school exposure and asthma morbidity in children. This review will focus on common school environmental exposures (cockroach, rodents, cat, dog, classroom pets, dust mite, fungus, and pollution) and their impact on children with allergies and asthma. Understanding and evaluation of school based environments is needed to help guide school-based interventions. School-based interventions have the potential for substantial benefit to the individual, school, community, and public health. However, there is a paucity data on school-based environmental interventions and health outcomes. The studies performed to date are small and cross-sectional with no control for home exposures. Randomized controlled school-based environmental intervention trials are needed to assess health outcomes and the cost-effectiveness of these interventions. The School Inner-City Asthma Intervention Study (SICAS 2), a NIH/NIAID randomized controlled clinical trial using environmental interventions modeled from successful home-based interventions, is currently underway with health outcomes results pending. If efficacious, these interventions could potentially help further guide school-based interventions potentially with policy implications. In the meanwhile, the Allergist/Immunologist can continue to play a vital role in improving the quality of life in children with allergies and asthma at school through the use of the ADA policy and Section 504 of the Rehabilitation Act as well as encouraging adoption of toolkits to build successful school-based asthma programs and asthma-friendly schools.